Training whilst under quarantine: Quick and effective warm-up for your daily dose of outdoor exercise - Edwards, A. (University of Cambridge, 2020)
For many, including myself, going out for a jog is often the only reason for setting foot outside right now. For this reason, several people have increased their volume of running training. At this time, I want to stress the importance of a warm-up for these activities. The main aim is always to benefit subsequent performance and reduce risk of injury. I also think a warm-up has the potential to achieve more than just the short-term benefits. A carefully selected routine can also help with the alleviation of "niggles", as well as stiff, and sore areas caused by prior conditions (e.g. that run you did earlier in the week or prolonged periods sat at the desk).